2019
DOI: 10.1002/edm2.76
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cardiovascular disease and antidiabetes treatment characteristics among a large type 2 diabetes population in the United States

Abstract: Objectives The purpose of this study was to assess atherosclerotic cardiovascular disease (ASCVD) prevalence, antidiabetes medication usage and physician specialty encounters among individuals with type 2 diabetes mellitus (T2DM) in the United States during 2015. Design Retrospective, cross‐sectional analysis. Patients Adults with T2DM in a large US administrative claims database. Patients were divided into ASCVD and non‐ASCVD groups. Subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 19 publications
8
40
3
Order By: Relevance
“…The leading cause of death in people with T2DM is CVD, therefore prevention of cardiovascular events is a key focus in the management of T2DM patients [1]. Several observational studies have shown that the use of antidiabetic drugs with demonstrated cardiovascular benefits in these patients is far from optimal, even in patients controlled by specialists [17,18]. This was also the case in our study: SGLT2i and GLP1ra were infrequently prescribed in patients with CVD (2.6% and 1.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leading cause of death in people with T2DM is CVD, therefore prevention of cardiovascular events is a key focus in the management of T2DM patients [1]. Several observational studies have shown that the use of antidiabetic drugs with demonstrated cardiovascular benefits in these patients is far from optimal, even in patients controlled by specialists [17,18]. This was also the case in our study: SGLT2i and GLP1ra were infrequently prescribed in patients with CVD (2.6% and 1.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Despite scientific evidence from a number of cardiovascular outcome trials (CVOTs) [7][8][9] and the guideline recommendations [2][3][4][5][6], adequate management of these patients remains beset with challenges. Several observational studies performed around the world report a gap between guideline recommendations and daily clinical practice [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…ASCVD was defined based on relevant ICD-9/-10 codes corresponding to diagnoses included in the ADA 2017 definition of ASCVD, including: acute coronary syndrome, history of MI, stable or unstable angina, peripheral arterial disease presumed to be of atherosclerotic origin, stroke, transient ischemic attack, and coronary or other arterial revascularization [17]. A detailed listing of relevant ICD-9/-10 codes has been provided elsewhere [15].…”
Section: Study Cohortsmentioning
confidence: 99%
“…The current study was designed to further the understanding of the impact of ASCVD on healthcare resource utilization and costs in patients with T2DM in the United States (US) using a large (1 million+) population identified within a national claims database. The clinical characteristics and antidiabetes treatment patterns of this population have been analyzed separately and reported elsewhere [15].…”
Section: Introductionmentioning
confidence: 99%
“…The claims database population used in the current study has been described previously . Briefly, eligible individuals were aged ≥18 years on 1 January 2015 and had an established diagnosis of type 2 DM before 1 January 2015, defined as ≥2 diagnoses for type 2 DM, based on international classification of diseases, ninth revision (ICD‐9) codes of 250.×0 or 250.×2 or ICD‐10 codes of E11.xx or ≥1 type 2 DM diagnosis with ≥1 oral antidiabetes drug claim, and no more than 1 type 1 diabetes diagnosis according to ICD‐9 (250.×1, 250.×3) or ICD‐10 (E10.×) codes.…”
Section: Participants and Methodsmentioning
confidence: 99%